Five new species of Drymeia Meigen from the Tibet Plateau, China (Diptera: Muscidae) - Xue, Wan-Qi; Wang, Dan-Dan; Zhang, Xue-Zhong; Xiang, Chao-Qun (Zootaxa, 2007)
Five new species of Drymeia Meigen are described from China, namely Drymeia naticerca Xue & Xiang, sp. nov., Drymeia nudiapica Xue & Zhang, sp. nov., Drymeia minutifica Xue & Wang, sp. nov., Drymeia spinicosta Xue & Xiang, sp. nov.., and Drymeia pilifemorata Xue & Wang, sp. nov. A generic diagnosis of Drymeia is given along with a key to the males of the 45 species of the genus presently known from China.